Pemanfaatan Website Profile Sebagai Sarana Informasi dan Promosi Usaha Porang Agrotanijaya Pacitan - Sri Anardani; Puguh Jayadi; Latjuba Sofyana STT; Gilang Romadhon (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The Agrotanijaya porang business is a porang tuber processing business located in Kebondalem Village, Tegalombo District, Pacitan Regency. Currently, the marketing process for Agrotanijaya's processed products is conventional, namely entrusting it to food stalls, depots and grocery stores. The marketing system currently implemented has the problem that Agrotanijaya products are less widely known. The solution offered is the development of a website portal as an internet media facility which can display profile information from Agrotanijaya. The activity method begins with the preliminary study, implementation and evaluation stages. Based on the evaluation results, it shows that on average over 80% of participants are able to use the features on the website independently.